Pharmacological effects of Sesamum indicum; Systematic review - Deepthika, S.H.K.; Karunagoda, K.P.K.R.; Perera, P.K. (Sri Lanka Association for the Advancement of Science, 2023)
Sesamumindicum L. is a wildly used medicine in Ayurveda and traditional medicine in Sri Lanka. This study aims to analyse the most recent research findings about the pharmacological effects of S. indicum. The PubMed, Scopus, and Cochrane library databases were searched extensively and systematically for papers published between January 2011 and May 2022. We considered the PRISMA Statement to provide a good structure for systematic reviews. The keywords used to search for articles included "Sesamumindicum." Other filters were selected as the limit to medicine, open access, full-text articles, journal articles, and written English. All the data were recorded in an excel sheet, and the following number of research articles were found in the various databases; PubMed (n=03), Cochrane library (n=39), and Scopus (n=75). After removing duplicates, there were 114 articles. Those articles were further screened, firstly by reading topics and abstracts and secondly by reading the full text, and which did not match the inclusions were removed. After removing those articles, there were 27 articles, and after adding 03 additional articles, 30 articles were included in the systematic review. Finally, 08 clinical trials, 11 in-vivo, and 15 in-vitro research were analysed. According to those studies, its anti-cancer activity, antioxidant activity, antibacterial activity, antiatherosclerosis activity, anti-inflammatory activity, analgesic activity, anti-allergic activity, menstrual bleeding-inducing effect, skin whitening effect, neuroprotective activity, etc., have been proven scientifically. Limitations such as limited clinical research, not claiming all pharmacological actions, and not testing some medicinally used parts were identified.
Keywords: Pharmacological effects; Sesamumindicum; Systematic reviews